Multimedia Development Life Cycle Method In Village Infographic Video - Noferianto Sitompul (Jurnal Mantik, 2022)
Sambas Regency is part of the province of West Kalimantan, whose administrative area includes 19 sub-districts with a total of 183 villages. If viewed from the number of towns, the exciting thing that becomes information for the needs of the community is informed about the development of each city, both in terms of facilities and infrastructure, community life to the number of residents in the village. Currently, information on village data such as population, average occupation, existing facilities and infrastructure, village vision, and mission can be obtained by asking directly to the village office for the form of the information displayed in the form of a village profile report document. This information search is categorized as less effective because it must come directly and takes a long time in the data search process. For this reason, it is necessary to visualize village information through infographic videos developed in motion graphics by applying the Multimedia Development Life Cycle method. Before publishing the infographic video, it was first tested by five material experts, and 18 village communities. The results of this study will get infographic videos of 10 villages in the Sambas district in MP4 format with a duration of 10 minutes.